Unique metabolic phenotype and its transition during maturation of juvenile male germ cells. Issue 5 (3rd April 2021) - Voigt, Anna Laura; Kondro, Douglas Andrew; Powell, Diana; Valli‐Pulaski, Hanna; Ungrin, Mark; Stukenborg, Jan‐Bernd; Klein, Claudia; Lewis, Ian A.; Orwig, Kyle E.; Dobrinski, Ina
Abstract: Human male reproductive development has a prolonged prepubertal period characterized by juvenile quiescence of germ cells with immature spermatogonial stem cell (SSC) precursors (gonocytes) present in the testis for an extended period of time. The metabolism of gonocytes is not defined. We demonstrate with mitochondrial ultrastructure studies via TEM and IHC and metabolic flux studies with UHPLC‐MS that a distinct metabolic transition occurs during the maturation to SSCs. The mitochondrial ultrastructure of prepubertal human spermatogonia is shared with prepubertal pig spermatogonia. The metabolism of early prepubertal porcine spermatogonia (gonocytes) is characterized by the reliance on OXPHOS fuelled by oxidative decarboxylation of pyruvate. Interestingly, at the same time, a high amount of the consumed pyruvate is also reduced and excreted as lactate. With maturation, prepubertal spermatogonia show a metabolic shift with decreased OXHPOS and upregulation of the anaerobic metabolism‐associated uncoupling protein 2 (UCP2). This shift is accompanied with stem cell specific promyelocytic leukemia zinc finger protein (PLZF) protein expression and glial cell‐derived neurotropic factor (GDNF) pathway activation. Our results demonstrate that gonocytes differently from mature spermatogonia exhibit unique metabolic demands that must be attained to enable their maintenance and growth in vitro.